Myocardial constructive work is impaired in cardiac amyloidosis, eases the differential diagnosis and predicts the prognosis among patients with left ventricular hypertrophy. (25th November 2020) - Palmiero, G; Rubino, M; Monda, E; Caiazza, M; Pafundi, P.C; Caso, V.M; Pacileo, G; Caso, P; Limongelli, G
Abstract: Background: Myocardial Work (MW) is a novel non-invasive echocardiographic method for myocardial performance assessment. MW is abnormal in patients with many forms of left ventricular hypertrophy [hypertrophic cardiomyopathy (HCM), hypertensive cardiomyopathy (HypCM), aortic stenosis (AS)] while little is known about cardiac amyloidosis (CA). Purpose: We aimed to evaluate the role of MW in myocardial performance assessment, diagnostic significance and prognostic relevance in CA patients. Methods: 25 patients with CA (10 AL pts and 15 ATTRwt pts) and 75 patients with LVH (25 HCM pts, 25 HypCMP pts, 25 pts mild AS pts) were enrolled. Beside routine measurements, deformation parameters [GLS (Global Longitudinal Strain), EFSR (Ejection Fraction on Strain Ratio), RRSR (Relative Regional Strain Ratio)], and MW parameters [MWI (Myocardial Work Index), GCW (Global Constructive Work), GWW (Global Wasted Work), GWE (Global Work Efficiency)] for LV function evaluation were analysed. Results: LV and RV function evaluated with classical and novel parameters were significantly impaired in CA group (see table). Among all these parameters, GCW showed the best performance to discriminate CA from other forms of LVH (AUC 0.90; 95% CI: 0.80–0.99; P<0, 0001), with a cut-off value <1141 mmHg% showing good sensitivity and specificity (90% and 82%, respectively). At Kaplan-Meier estimation of cardiovascular mortality there were 9 deaths in the CA group and none in LVH group, showed significantly higher mortality at follow-up (p=0, 0001). At multivariate analysis GCW (β=1, 006; 95% CI: 1, 003–1, 009; P<0, 0001) was the only prognostic parameter associated with cardiovascular mortality. Discussion: Myocardial performance was reduced in CA group. GCW was able to discriminate CA from other forms of LVH and showed to be an independent prognostic factor. In our pilot study GCW seems a promising novel diagnostic and prognostic factor in CA. Funding Acknowledgement: Type of funding source: None